2022
DOI: 10.1021/acsami.1c22514
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Selective Gold Recovery Based on Hypercross-Linking and Polyamine-Functionalized Porous Organic Polymers

Abstract: With the continuous increase of electronic products, there is an urgent need to effectively recover gold from e-waste and other secondary resources other than the original mine. Here, hypercross-linking and polyamine-functionalized porous organic polymers (Pc–POSS–POP) were designed and facially synthesized based on multiple azo-coupling polymerizations between 2,9,16,23-tetraaminophthalocyanine (H2Pc­(NH2)4) and octa­(aminophenyl)-t8-silsesquioxane (OAPS) for the first time. The reaction requires no metal as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…From the EDS images, the elements of C, O, N, and Au are dispersed uniformly in PCS-PAA. According to previous reports, the reduction reaction occurs during the adsorption of Au­(III) by the adsorbent. , …”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…From the EDS images, the elements of C, O, N, and Au are dispersed uniformly in PCS-PAA. According to previous reports, the reduction reaction occurs during the adsorption of Au­(III) by the adsorbent. , …”
Section: Resultsmentioning
confidence: 86%
“…According to previous reports, the reduction reaction occurs during the adsorption of Au(III) by the adsorbent. 53,54 3.8. Catalytic Application of PCS-PAA-Au.…”
Section: Adsorption Mechanism Of Au(iii)mentioning
confidence: 99%
See 2 more Smart Citations
“…5 However, electronic waste (e-waste) is considered one of the most attractive sources of gold due to its high content of precious metals. 6,7 Research has showed that one ton of abandoned mobile phones contains about 347 g of gold, and the gold content of 40 mobile phones is equivalent to mining 1 ton of ore, so it can be seen that e-waste is a "gold mine" that is still to be mined. [8][9][10] According to data from the International Telecommunication Union, a record 53.6 million tons of e-waste was generated worldwide in 2019, and this will rise to 74.7 million tons by 2030.…”
Section: Introductionmentioning
confidence: 99%